2014
DOI: 10.1590/s0080-6234201400002000021
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Resulted From Breastfeeding: A New Approach To A Known Problem

Abstract: Injuries resulted from breastfeeding: a new approach to a known problemCervellini MP, Gamba MA, Coca KP, Abrão ACFV RESUMENEste estudio tuvo como objetivo analizar las grietas del pezón causadas por el amamantamiento bajo el enfoque dermatoló-gico. Se realizaron dos revisiones integradoras de la literatura, una relacionada con definiciones, clasificaciones y métodos de evaluación de las lesiones en el pezón y otra sobre los estudios de validación relacionadas a esas temáticas. En la primera se incluyeron 20 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 18 publications
(53 reference statements)
0
32
0
6
Order By: Relevance
“…[10][11][12] In relation to the types of nipple injuries, there is no consensus as regarding to the degree of impairment of the tissue layer on the nipple-areola region. 13,14 The lack of clinical definition for nipple trauma results in disagreements, up to a point that its diagnosis and treatment may be compromised. 14 It is suggested that in the context of assisting nursing mothers, nipple trauma may be defined as an alteration in the normal anatomy of the nipple skin with the presence of a primary lesion caused by the modification of the color or thickness and not only as a solution of continuity on the skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] In relation to the types of nipple injuries, there is no consensus as regarding to the degree of impairment of the tissue layer on the nipple-areola region. 13,14 The lack of clinical definition for nipple trauma results in disagreements, up to a point that its diagnosis and treatment may be compromised. 14 It is suggested that in the context of assisting nursing mothers, nipple trauma may be defined as an alteration in the normal anatomy of the nipple skin with the presence of a primary lesion caused by the modification of the color or thickness and not only as a solution of continuity on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…14 It is suggested that in the context of assisting nursing mothers, nipple trauma may be defined as an alteration in the normal anatomy of the nipple skin with the presence of a primary lesion caused by the modification of the color or thickness and not only as a solution of continuity on the skin. 14 The location of the lesion is observed in the upper part of the body and around the base of the nipple, more often found at the tip of the nipple 10,12,15 involving dermis and epidermis with the presentation in the form of linear ulceration or curved. 13 The woman presents symptoms of severe pain on the nipples during breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…The type and severity of nipple injury are affected by subjective factors. There is no uniform consensus on the de nition, classi cation, and evaluation methods of nipple injury [8] . There is currently no highquality research on the treatment of nipple injury [9] .…”
Section: Discussionmentioning
confidence: 99%
“…This is a cause for concern, because breast problems are a determining factor for breastfeeding abandonment, due to the pain and discomfort they can cause [15].…”
Section: Discussionmentioning
confidence: 99%